Electrolyte Inertia In Chronic Kidney Disease - Sourabh Sharma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Electrolyte imbalances are a common and challengingaspect of managing chronic kidney disease (CKD). Despiteadvances in treatment, a phenomenon known as"electrolyte inertia"- the inertness to correcting abnormalelectrolyte levels- may persist in CKD patients. This inertiacan result from various factors which include delayedtherapeutic intervention, the complexity of multiple coexistingcomorbidities, and the judicious balancedtherapeutic approach necessitated by the multidyselectrolytaemiain CKD management. Through theconcept of “electrolyte inertia,” we explore the underlyingcauses for this phenomenon, its clinical implications, andstrategies to overcome it, to achieve better patient care inCKD. Keywords: Chronic kidney disease, electrolytes,hyperkalaemia, hyperphosphataemia, hypocalcaemia,hyponatraemia